2018
DOI: 10.1371/journal.pone.0191804
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic re-immunization of off-treatment childhood cancer survivors: An implementation feasibility study

Abstract: There are no universally approved re-vaccination guidelines for non-transplant pediatric cancer survivors. We hypothesized that by utilizing a response-based re-vaccination schedule, we could tailor vaccine schedules in off-treatment cancer survivors. Pre-vaccination antibody levels were obtained in 7 patients at an average of 20 days after the end of treatment date. In those without protective antibody levels, we administered vaccines 3 months after completion of treatment. Revaccinating patients 3 months aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Previous studies have also shown different rates in loss of immunity for different VPDs within the same patient population. 5,6,8,9,12,18 -26…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also shown different rates in loss of immunity for different VPDs within the same patient population. 5,6,8,9,12,18 -26…”
Section: Discussionmentioning
confidence: 99%
“…Han and colleagues show pilot data that immune recovery in patients treated with chemotherapy may be earlier than previously expected and showed safety with reimmunization at 3 months after cessation of chemotherapy. 23 More studies are needed to show early ALC recovery and its relationship with seroresponse to vaccinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that a universal one dose schedule of revaccination is bene cial. 10,11 In uenza vaccinations are also recommended for patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines generally suggest that most children with cancer begin to receive routine or catch-up vaccines once immunological recovery is complete, approximately 3–6 months following the completion of chemotherapy depending on the type of treatment administered, immunological recovery, and type of vaccine (attenuated vs. non-attenuated) [ 2 – 4 ]. Recent research suggests that among survivors who have not undergone bone marrow transplantation, receipt of attenuated vaccines as early as three months after treatment might result in protective antibody responses [ 5 ]. However, this research is based on small samples of patients in a limited age range.…”
Section: Introductionmentioning
confidence: 99%